2020
DOI: 10.1002/dad2.12028
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic correlates of prevalent mild cognitive impairment and Alzheimer's disease in adults with Down syndrome

Abstract: Introduction Disruption of metabolic function is a recognized feature of late onset Alzheimer's disease (LOAD). We sought to determine whether similar metabolic pathways are implicated in adults with Down syndrome (DS) who have increased risk for Alzheimer's disease (AD). Methods We examined peripheral blood from 292 participants with DS who completed baseline assessments in the Alzheimer's Biomarkers Consortium–Down Syndrome (ABC‐DS) using untargeted mass spectrometry (MS). Our sample included 38 individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 130 publications
(277 reference statements)
0
10
0
Order By: Relevance
“…Therefore, by use of the A/T(N) framework, it is anticipated that we will be able to conduct clinical trials in a more finely characterized participant sample. 20,36,41,42, we estimate that, between ages 35 to 55 years, there will be 80% A+, 40% T+, and 10% (N)+ for cognitively stable adults with DS; 80% A+, 60% T+, and 20% (N)+ for MCI-DS; and 80% A+, 80% T+, and 60% (N)+ for dementia in the DS group (Figure 1).…”
Section: Neurodegeneration (N)mentioning
confidence: 94%
See 2 more Smart Citations
“…Therefore, by use of the A/T(N) framework, it is anticipated that we will be able to conduct clinical trials in a more finely characterized participant sample. 20,36,41,42, we estimate that, between ages 35 to 55 years, there will be 80% A+, 40% T+, and 10% (N)+ for cognitively stable adults with DS; 80% A+, 60% T+, and 20% (N)+ for MCI-DS; and 80% A+, 80% T+, and 60% (N)+ for dementia in the DS group (Figure 1).…”
Section: Neurodegeneration (N)mentioning
confidence: 94%
“…We intend to look at AT(N) classification across the different clinical diagnostic categories, that is, Cognitively Stable, Mild Cognitive Impairment, and Dementia in the ABC‐DS Study to calculate A+/T+/(N)+ prevalence and to correlate the various classifications with clinical and cognitive status. Based on a review of the literature, 20,36,41,42,59‐93 we estimate that, between ages 35 to 55 years, there will be 80% A+, 40% T+, and 10% (N)+ for cognitively stable adults with DS; 80% A+, 60% T+, and 20% (N)+ for MCI‐DS; and 80% A+, 80% T+, and 60% (N)+ for dementia in the DS group (Figure 1).…”
Section: Estimating A+/t+(n)+ Prevalence In Dsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an increasing interest in defining the precise metabolic pathways involved in the pathogenesis of AD 9 , 16 19 . A significant correlation between reduced brain regional glucose metabolism and decreased α-ketoglutarate dehydrogenase complex (KGDHC) 20 , 21 has been described in AD.…”
Section: Introductionmentioning
confidence: 99%
“…3 70 . Xenobiotic Metabolic Processes are specific to Severe AD modules only, and studies 61 found links between dementia progression and various metabolic pathways.…”
Section: Gene Co-expression Network Analysis Reveals Gene Expression Dynamics For Ad Phenotypes Across Multiple Brain Regionsmentioning
confidence: 99%